PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL, DAN KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN TERHADAP KOEFISIEN RESPON LABA YANG DIMODERASI KONSERVATISME AKUNTANSI - Sugi Suhartono (Jurnal Ekonomi Perusahaan, 2015)
Of this study aimed to learn whether of company’s size, capital structure, and timeliness of financial reports to the earnings response coefficient moderated by accounting conservatism on companies listed on Indonesia Stock Exchange in the period 2010-2012. The population in this study are manufacturing companies listed in Indonesia Stock Exchange in the period 2010 to 2012,  amounting to 148 companies. The sample selection is done by purposive sampling method,  and obtained a sample of 120 companies in this study. The results of this study show that (1) the size of the company negatively affects earnings response coefficient, (2) capital structure negatively affects earnings response coefficient, (3) accounting conservatism positively affects on earnings response coefficient, (4) while the variable timeliness of financial report does not significantly affects to earnings response coefficient, (5) accounting conservatism strengthens the negative relationship between company’s size on earnings response coefficient, (6) the accounting conservatism weakens the negative relationship between capital structure on earnings response coefficient, (7) accounting conservatism moderates the relationship between timeliness of financial statements with earnings response coefficients.